Protective immunity against COVID-19: Unravelling the evidences for humoral vs. cellular components - Priyanka; Choudhary, Om Prakash; Singh, Indraj (Travel medicine and infectious disease, 2021)
Once severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters the host via contact, droplet or aerosol-mediated transmission [1], the non-specific innate immune response is followed by antigen-specific adaptive immunity mediated by B cells (humoral immunity) producing neutralizing antibodies and T cells (cellular immunity) including CD8+, CD4+ and regulatory T cells. In an outbreak with 85% attack rate, the neutralizing antibodies from previous SARS-CoV-2 infection were significantly associated with protection against re-infection (also observed in animal models like rhesus macaques) [3]. The present-day caveat is waiving off of immunity passports and compliance of mitigation measures by recovered patients as diligently as the unexposed population at risk.Ethical approval This article does not require any human/animal subjects to acquire such approval.Funding There is no funding source used for this paper.CRediT authorship contribution statement Priyanka: Conceptualization, Data curation, Visualization, Writing - original draft, Writing - review & editing.